Investigations on the replacement of bismaleimide by the bio-based bisitaconimide for recyclable thermoset composites based on thermo-reversible Diels-Alder cross-links. (15th May 2020) - Lejeail, M.; Fischer, H.R.
Graphical abstract: Highlights: Sustainable thermosets by substitution of oil-based components by "green" monomers. Thermo-reversibility of the network makes crosslinked materials re-mendable after a damaging event and ultimately recyclable. Elongation of the lifetime by complete recyclability at the end of the lifetime. Abstract: Stimulated by the growing demand for more sustainable polymers, explorative experiments were performed to substitute oil-based components by "green" monomers derived from bio-based compounds to decrease the carbon footprint of the production of such thermosets. The potential of itaconimides synthesised from itaconic anhydride e.g. obtained by fermentation of carbohydrates or by pyrolysis of citric acid and as such easily accessible from inexpensive renewable raw materials for DA based epoxy materials as well as their action to achieve retro DA switching temperatures as low as 80 °C was explored. Composites were manufactured using this new resin and mechanically tested. The thermo-reversibility of the network makes the crosslinked materials re-mendable after a damaging event and ultimately recyclable. In such a way the sustainability of the material can be improved as well as by using bio-based starting materials, by elongation of the lifetime and by complete recyclability at the end of the lifetime.